Respon Pertumbuhan Dan Produksi Tanaman Siomak (Lactuca Sativa L.) Pada Variasi Media Tanam Dan Pupuk Urin Kelinci - Mardiana, Yushi; Bayu Prasetyo, Ahmad; Rahmatika, Widyana (JURNAL ILMIAH AGRINECA, 2025)
Siomak is a type of lettuce plant that has a slightly different leaf shape from lettuce plants in general. This research aims to determine the interaction between planting media treatment and rabbit urine fertilizer concentration on the growth and yield of siomak plants. This research was carried out from April to May 2022 in Rejomulyo Village, Kras District, Kediri Regency, East Java Province. This research used a factorial completely randomized design (CRD) with two factors. The first factor is the planting medium (M), while the second factor is the concentration of rabbit urine fertilizer (K). The results of this research show that the M2K4 treatment combination (planting media ratio 2:1:3 + 40 ml/L urine fertilizer) is the treatment combination with the best results in the observation variables of number of leaves and wet weight per plant. The combination of M2K2 treatment (planting media ratio 2:1:3 +20 ml/L urine fertilizer) is the combination with the best results in increasing the root length of siomak plants. The single treatment of M2 planting media (planting media ratio 2:1:3) showed better results than the results of treatment M1 (planting media ratio 2:1:2) significantly in the observation variables of plant height, number of leaves, leaf area and root volume. . K4 treatment (urine fertilizer 40 ml/L) is the most effective and efficient concentration in increasing plant height and leaf area growth. The results of observing the root volume of the K5 treatment (50 ml/L urine fertilizer) showed the best results.